Unilateral spatial neglect - Soroker, Nachum (Rehabilitacija (Ljubljana), 2012)
This paper provides a review of two aspects of unilateral spatial neglect (USN): theoretical accounts of USN as one of the most puzzling conditions encountered in rehabilitation clinical practice, and strategies to enhance conscious perception in the neglected side. Following a short description of the symptom complex, there is a review of clinical and basic research on USN performed at the Loewenstein Rehabilitation Hospital in Raanana, Israel.
Keywords: clinical rehabilitation; klinična rehabilitacija; neurology; nevrologija; Perceptual Disorders; raziskave; research; theory; unilateral spatial neglect; zanemarjanje prostora v polovici vidnega polja; zaznavanje; zaznavne motnje